2009
DOI: 10.1097/meg.0b013e32832183cf
|View full text |Cite
|
Sign up to set email alerts
|

Tropical calcific pancreatitis and its association with CTRC and SPINK1 (p.N34S) variants

Abstract: The contribution of CTRC variants to TCP is relatively small, but the identification of novel loss-of-function variants (p.G61R) underscores the importance of the trypsinogen pathway in causing TCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 26 publications
1
19
1
Order By: Relevance
“…A recent multi-centre study showed chymotrypsin C gene mutation to be associated with idiopathic CP in Western as well as Indian patients lending further support to the genetic theory of aetiopathogenesis of idiopathic CP 38 39. This is important because it puts a big question mark about the term ‘tropical pancreatitis’ which has a geographical rather than aetiological connotation.…”
Section: Discussionmentioning
confidence: 82%
“…A recent multi-centre study showed chymotrypsin C gene mutation to be associated with idiopathic CP in Western as well as Indian patients lending further support to the genetic theory of aetiopathogenesis of idiopathic CP 38 39. This is important because it puts a big question mark about the term ‘tropical pancreatitis’ which has a geographical rather than aetiological connotation.…”
Section: Discussionmentioning
confidence: 82%
“…SPINK1 gene mutations have been reported to be common in Indian patients with TCP [4,10,20,21]. In fact, one study found that 42 % of these patients had SPINK1 mutation, 9 % had CFTR gene mutation, and 41 % had CFTR gene polymorphisms [4,10].…”
mentioning
confidence: 99%
“…Rosendahl et al also investigated the role of CTRC variants in patients of Indian origin and found them to be associated with TCP, which was further substantiated in another study 18. However, both the studies have focused on a small number of subjects 16 18. We screened the complete coding region of CTRC in a large population of CP patients from India, using a case-control cohort approach and also analysed its interaction with other susceptibility genes like SPINK1 that are associated with CP in Indians.…”
Section: Introductionmentioning
confidence: 71%
“…Rosendahl et al also investigated the role of CTRC variants in patients of Indian origin and found them to be associated with TCP, which was further substantiated in another study 18. However, both the studies have focused on a small number of subjects 16 18.…”
Section: Introductionmentioning
confidence: 86%